1988
DOI: 10.1128/jvi.62.3.962-969.1988
|View full text |Cite
|
Sign up to set email alerts
|

B-cell lymphoproliferation and lymphomagenesis are associated with clonotypic intracellular terminal regions of the Epstein-Barr virus

Abstract: We analyzed 17 B-cell lineages cloned from two patients with infectious mononucleosis and found that different B-cell lineages exhibited notable variation in the length of the fused Epstein-Barr virus (EBV) terminal region on intracellular EBV episomes. EBV termini in different B-cell clones from the same person differed by as many as 15 to 20 reiterations of the ca. 500-base-pair terminal repeat sequence. In contrast, analysis of seven B-cell lineages cloned from a patient with a fatal, oligoclonal lymphoma r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…This finding suggests that the EBER2‐PAX5 complex interacts stably with the TR regions and only prolonged depletion disturbs its regulatory role. We thus speculate that EBER2‐PAX5 is involved in properly organizing the viral chromatin, especially the direct tandem repeats of the TR regions, which are present at up to 20 copies per episome . As EBV episomes are also present in multiple copies (up to 50) in an infected cell , improper genome organization could result in deleterious genome instability; the repeat regions could potentially recombine with those from other episomes .…”
Section: Why Does the Ebv Life Cycle Need A Ncrna?mentioning
confidence: 98%
“…This finding suggests that the EBER2‐PAX5 complex interacts stably with the TR regions and only prolonged depletion disturbs its regulatory role. We thus speculate that EBER2‐PAX5 is involved in properly organizing the viral chromatin, especially the direct tandem repeats of the TR regions, which are present at up to 20 copies per episome . As EBV episomes are also present in multiple copies (up to 50) in an infected cell , improper genome organization could result in deleterious genome instability; the repeat regions could potentially recombine with those from other episomes .…”
Section: Why Does the Ebv Life Cycle Need A Ncrna?mentioning
confidence: 98%
“…Cloned EBV-DNA fragments were the kind gift of Dr. L. Rymo. A 1.9-kb Xhol subfragment of the EcoRI-Dhet fragment was used for TR probing (Brown et al, 1988). A 0.9-kb SacII-BamHI subfragment of the BamHI C fragment and the BamHI W, H and E fragments were used to assess the methylation status of the viral genome.…”
Section: Dna Preparation and Analysismentioning
confidence: 99%
“…Each new circularization event leads to a differently sized TR fragment (Given et al, 1979;Kintner and Sugden, 1979;Raab-Traub and Elynn, 1986). Only one such fragment is present in each clonal cell line, established by a single infectious event (Brown et al, 1988;Hurley and Thorley-Lawson, 1988). Ernberg et al (1989) have found that EBV-genomes are highly methylated in a Burkitt lymphoma (BL) line and in a nude-mouse-passaged NPC tumor.…”
mentioning
confidence: 99%
“…The clonality of EBV-associated B-cell lymphoproliferative disease may have implications for diagnosis, prognosis, and therapy [Chadburn et al, 1997]. Tumor clonality is typically assessed by one of two methods: either analysis of the genomic structure of the cellular immunoglobulin gene (JH rearrangement assay) or analysis of the structure of the EBV genome terminal repeat region (EBV termini assay) [Brown et al, 1986[Brown et al, , 1988Raab-Traub and Flynn, 1986;Cleary et al, 1988]. A review of the published literature suggests that the results of the JH rearrangement assay and the EBV termini assay are often concordant for the same tumor specimen [Brown et al, 1988;Cleary et al, 1988;Locker and Nalesnik, 1989;Patton et al, 1990;McGrath et al, 1991;Neri et al, 1991;Gulley et al, 1992;Cen et al, 1993;Craig et al, 1993;Delecluse et al, 1993;Shibata et al, 1993;Knowles et al, 1995;Mandell et al, 1999;Ohshima et al, 1999], but numerous examples of discordant results have been noted [Locker and Nalesnik, 1989;Patton et al, 1990;McGrath et al, 1991;Cen et al, 1993;Delecluse et al, 1993;Knowles et al, 1995;Ohshima et al, 1999;Sadahira et al, 2001;Nador et al, 2003].…”
Section: Introductionmentioning
confidence: 99%